Special Economic Zones and household welfare: New evidence from Ghana - Charles Ackah; Robert Darko Osei; Nana Y. A. Owusu; Vera Acheampong (Kiel Centre for Globalization (KCG), 2023)
The study evaluates the impact of Special Economic Zones (SEZs) on household welfare (per capita consumption expenditure (PCE) and poverty status) in Ghana using the Ghana Socioeconomic Panel Survey Dataset. SEZs spillover effect on household welfare within a binary treatment condition may lead to finding inadequacy for policy. Therefore, in this study, a paired Propensity Score Matching (PSM) and an Augment Inverse Probability Weighing (AIPW) for multivalued treatment effect (MTE) models were used to correct the potential selection bias and to estimate the effect of SEZs on household poverty. Households located within 30km radius near SEZs seems to have an improved PCE and reduced poverty compared with households farther away. The results on the poverty effect using different household characteristics provide a strong basis for a deeper understanding of the heterogeneous state of SEZs and poverty in Ghana. While data limitations prevented the study from drawing conclusions on the direct channels at work, it was able to investigate the indirect channels, which suggests that SEZs in Ghana may induce employment restructuring effects for individuals in paid employment or farming, albeit for different reasons, which can have important implications for the SEZ-employment-poverty relationship.
Keywords: I31; L52; 330; Special Economic Zones; Household; Poverty; Propensity Score Matching; Ghana